Perancangan Informasi Batik Solo Berbasis Bootstrap - Adhiasta, Mohamad Rizky; , Muhammad Kusban, S.T.,M.T (2016)
Batik Solo is one kind of Indonesian cultural heritage that should be kept in existence. Many batik craftmen or entrepreneurs surely want to survive in the development era, though some of them could not keep up therefore an information system is required to help to increase batik selling in Solo. Designing an information later can be used as a development tool that gives information as well as location of batik seller. It is bootstrap based website that can give us information visualization together with it's location map around Solo. The final result of batik Solo website design is to become informative tool to find seller's location especially for buyer's or visitor of Solo. The value percentage of 10 respondent who reviewed this application were visual 85% simple layout, 72,4% of content have a good information, 67% of data mobility up to date and 66% speed load website page is enough. Those respondents supported this website and hoped to make use of it immediately.